Writing high-quality standard operating procedures - Mathur, Atul (Henry Stewart Talks, 2024)
Standard Operating Procedure (SOP) writing, SOP quality and snowball effect, Key attributes of SOPs, Purpose, scope, procedure and revision history, Best writing practices